2010
DOI: 10.1111/j.1365-2958.2010.07385.x
|View full text |Cite
|
Sign up to set email alerts
|

MmpS4 promotes glycopeptidolipids biosynthesis and export in Mycobacterium smegmatis

Abstract: SummaryThe MmpS family (mycobacterial membrane protein small) includes over 100 small membrane proteins specific to the genus Mycobacterium that have not yet been studied experimentally. The genes encoding MmpS proteins are often associated with mmpL genes, which are homologous to the RND (resistance nodulation cell division) genes of Gram-negative bacteria that encode proteins functioning as multidrug efflux system. We showed by molecular genetics and biochemical analysis that MmpS4 in Mycobacterium smegmatis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 51 publications
2
67
0
Order By: Relevance
“…For example, the inability to secrete the de novo synthesized siderophore, pyoverdine, a major virulence factor of P. aeruginosa, impairs its production (25). Likewise, MmpS4 connects biosynthesis enzymes for the synthesis of glycopeptidolipids, a major outer membrane lipid, with the transporter MmpL4 in M. smegmatis and, thus, couples biosynthesis and export (26). However, no interaction between the mycobactin biosynthesis enzyme G (MbtG) and MmpS4 was detected in crosslinking experiments in Mtb (14).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the inability to secrete the de novo synthesized siderophore, pyoverdine, a major virulence factor of P. aeruginosa, impairs its production (25). Likewise, MmpS4 connects biosynthesis enzymes for the synthesis of glycopeptidolipids, a major outer membrane lipid, with the transporter MmpL4 in M. smegmatis and, thus, couples biosynthesis and export (26). However, no interaction between the mycobactin biosynthesis enzyme G (MbtG) and MmpS4 was detected in crosslinking experiments in Mtb (14).…”
Section: Discussionmentioning
confidence: 99%
“…Deshayes et al (24) deleted mmpS4 in M. smegmatis, thereby causing a switch from smooth to rough morphology, although the mutant was still able to produce a small amount of a "GPL-like molecule." MALDI-TOF MS of the lipid extract from this mutant had a major peak 14 Da higher than that of the wild-type GPL.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed 8 genes in the GPL locus, including the genes in which spontaneous insertions/deletions (indels) were previously identified in rough M. abscessus clinical strains (mps1 and mmpL4b) (22) as well as those which when experimentally rendered nonfunctional resulted in a switch from smooth to rough in M. abscessus or M. smegmatis (gap, mps2, mbtH, mmpL4b, and mmpS4) (17,(23)(24)(25). fmt and mmpL4a were included because of their adjacency to the above genes (Fig.…”
Section: Phylogenetic Analysis Of the Clinical Isolates By Mlstmentioning
confidence: 99%
“…Five genes encoding MmpS proteins are adjacent to genes encoding MmpL proteins (8,13). Work in the model organism Mycobacterium smegmatis demonstrated that MmpS4 was required for bacterial sliding motility and biofilm formation (19). That the mmpS4 and mmpL4 mutants had similar phenotypes underscores a coordinated function for cognate MmpSMmpL proteins.…”
Section: Tuberculosis (Tb)mentioning
confidence: 99%